1963
DOI: 10.1002/hlca.19630460715
|View full text |Cite
|
Sign up to set email alerts
|

Recherches sur la synthèse des acides gras XIII. Influence de l'acétazolamide seul ou associé à l'insuline sur la synthèse in vivo des acides gras chez la souris

Abstract: Les diagrammes de solubilitk communiquks permettent de trouver toutes les valeurs numkriques (composition des solutions de roulement, ternpkrature de cristallisation, quantitCs d'eau B introduire et B kvaporer) nkcessaires 8. l'ktablissement d u n prockdk en cycle pour la prdparation de KH,PO, par ((double dkcompositiono selon KC1 + NaH,PO, = KH,PO, + NaC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

1965
1965
2000
2000

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…If radioactivity from citrate appears in fatty acids, the pathway for this conversion needs to be delineated. Reexamination of the data presented by Shrago, Spennetta, (46), it was found that carbonic anhydrase inhibitors could reduce the synthesis of fatty acids in vivo (47,48). For this reason we tested the possibility that a carbonic anhydrase inhibitor could inhibit lipogenesis in human adipose tissue.…”
Section: Discussionmentioning
confidence: 96%
“…If radioactivity from citrate appears in fatty acids, the pathway for this conversion needs to be delineated. Reexamination of the data presented by Shrago, Spennetta, (46), it was found that carbonic anhydrase inhibitors could reduce the synthesis of fatty acids in vivo (47,48). For this reason we tested the possibility that a carbonic anhydrase inhibitor could inhibit lipogenesis in human adipose tissue.…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon may be attributable in large part to the marked enhancement of monoene-synthesis that is produced by fat-free feeding. In mice maintained on this regime, over 40% of the fatty acids formed from labeled acetate is of the monounsaturated variety (30). An even more unsaturated spectrum of acids can be incorporated into liver and hence plasma triglyceride if acids synthesized in fat tissue and rapidly released into the blood are desaturated in the liver before being esterified.…”
Section: Methodsmentioning
confidence: 99%
“…En outre, les enzymes du mécanisme de synthèse des acides gras par condensation sont probablement altérés par cette substance, comme en témoigne la plus forte inhibition ren contrée pour l'acide palmitique. Néanmoins l'accroissement d'in hibition introduit par administration de bicarbonate (4) qui, on le sait, est indispensable au fonctionnement de ce mécanisme, comme cela a été démontré à la fois in vitro (12) et in vivo (9,24,25), semble infirmer une action directe ou unique sur ces enzymes.…”
Section: Discussionunclassified
“…L'insuline contrôlerait et favoriserait de façon plus spécifique la synthèse de l'acide oléique (2,15). Cette action pourrait résulter d'un accroissement de la dégradation oxydative de glucose qui fournirait un NADPH plus directement orienté vers la synthèse de l'acide oléique (24). Or c'est l'acide palmitique qui a été le plus inhibé.…”
Section: Discussionunclassified